2022
DOI: 10.9734/ajaees/2022/v40i121778
|View full text |Cite
|
Sign up to set email alerts
|

Market Integration and Price Transmission Analysis of Onion in Wholesale Markets of India

Abstract: The present study was done in seven major onion wholesale markets in India, namely Pimpalgaon, Lasalgaon, Solapur, Pune, Bangalore, Hyderabad and Indore to explore the interdependence of wholesale prices amongst Indian onion markets. The study was conducted in all India perspective and the study period involves the seventeen years data of onion wholesale prices (January 2004 to December 2020). The study was majorly based on the prices of onion obtained through secondary source. These data were collected from v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
3
4
0
Order By: Relevance
“…In the long run, the study suggests that the retail price of imported onion is not transmitted equally to the retail price of local onion, although in the short run, the transmission is equal. No prior similar study between import and local product market was found but the most relevant study revealed equal price transmission is possible between the wholesale and retail market [ 26 ] which align with this study result. The findings of the study imply that policymakers in Bangladesh must take into account the diverse dynamics of market adjustment when establishing policies to manage onion prices.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…In the long run, the study suggests that the retail price of imported onion is not transmitted equally to the retail price of local onion, although in the short run, the transmission is equal. No prior similar study between import and local product market was found but the most relevant study revealed equal price transmission is possible between the wholesale and retail market [ 26 ] which align with this study result. The findings of the study imply that policymakers in Bangladesh must take into account the diverse dynamics of market adjustment when establishing policies to manage onion prices.…”
Section: Resultssupporting
confidence: 84%
“…From the empirical results show that both the F statistics and t statistics value is greater than the upper bound value, indicating a long-term relationship between variables ( Table 3 ). The results of both the tests confirm that the variables in all three models are cointegrated, and for market asymmetry determination the variables should be cointegrated as suggested in prior research [ 7 – 9 , 11 , 24 , 26 ]. In addition, NARDL F-statistic [ 49 ] confirms that all the variables have long-run asymmetric association in the onion supply chain of Bangladesh.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…The Asian Bulletin of Green Management and Circular Economy SDGs 4(1),18-52 transmission and volatility are a valuable instrument for evaluating market integration, stability, and the prospect of disruptions. It additionally advises decision-makers about infrastructure needs and regulations to improve stability (Kumar et al, 2022;Muharam et al, 2019). Since fragmented food markets have little potential to allocate resources and respond to crises, they pose serious risks of inefficiency, less consumer preference, price volatility, and increased food insecurity (Baulch, 1997a).…”
Section: Issn (Print): 2959-0027mentioning
confidence: 99%